Implementation of Five Moments and Six Steps Hand Hygiene Among Nurses in Two Hospitals in South Sulawesi Province - Prayuda, Maesar; Tombong, Andi Baso (Media Keperawatan Indonesia, 2024)
Hand hygiene is a simple step that is most effective to prevent patients from HAIs in hospitals. Therefore, its practice must be implemented by healthcare providers continuously. Its compliance among nurses must always be monitored to optimise safe health care and services, protecting providers and patients during hospitalization. This study aims to identify the implementation of five moment's and six step's hand hygiene by nurses in the inpatient rooms of two hospitals with different ownership status in the South Sulawesi Province. The study used a descriptive quantitative method with an observational approach. This study used a quota sample of 76 nurses and used the WHO adaptation of the Hand Hygiene Compliance (KKT) observation sheet. The study found that the implementation of five moment's hand hygiene by nurses at Hospitals A and B accounted for 15.2% and 8.8%, respectively, and the implementation of six step's hand hygiene was 9.9% and 7%. Hand hygiene compliance by inpatient nurses at Hospital A and Hospital B is in the non-compliant category, not in accordance with WHO recommendations, which are ≥85%. Further research is recommended to focus on factors related to compliance in implementing hand hygiene in hospitals as well as research in developing programs to improve hand hygiene compliance for nurses in health care facilities.